IMPLEMENTASI STRATEGI PENERIMAAN PAJAK KENDARAAN BERMOTOR - ', Zulkafli (Jurnal Ilmu Administrasi Negara, 2016)
Implementation Strategies Motor Vehicle Tax. The purpose of research is to investigatethe implementation of the motor vehicle tax revenue in the Technical Implementation Unit(UPT) Income Rokan Hulu. The informants are officers motor vehicle tax recipients and taxpayers.Data were collected by interview, observation and documentation. Data analysis started fromthe data reduction, data presentation and conclusion. The results showed that in the implementationof strategies to increase tax revenues, motor vehicle has been running pretty well. But in itsimplementation still found that factors inhibiting factor means of building and budget.